A comparison study of Malay and Nyonya kebaya in the Peninsular of Malaysia from 1910 – 2017 / Zarina Yusof - Yusof, Zarinah (2021)
Baju Kebaya is a traditional costume worn by the ladies in the archipelago over the last 600 years. In Malaysia, it is worn with different styles by the Malay women, Nyonya Peranakan and Jawi Peranakan. However, the recent fashion style has somehow reformed its’ concept due to some cultural changes among these Malaysians. Therefore, this research was conducted to examine the comparative design, style and features found in the Baju Kebaya based on the historical literature, journals and visual documentation obtained from the libraries, museums, National Archive as well as private collections. In performing this study, a systematic qualitative research is conducted to document the manufacture, measurement and selection of the Baju Kebaya from 1910 to 2017. The literature review of current trends and research on the Baju Kebaya successfully traced the chronological development of this costume in the Peninsular of Malaysia. Unstructured interviews with the relevant key players in the Kebaya industry, including academicians, traditionalists, dressmakers and appreciators were carried out as well. The identification of the traditional distinctiveness of the Baju Kebaya was addressed by categorizing the clothes into different groups according to their style and character. The Baju Kebaya has also undergone several changes, including the cut and shape, length of the dress, fabric, style, and coordination. The findings suggested that there are similarities; in terms of function and structure and differences; in terms of choice of fabric and ornaments between the design of the Malay and Baba Nyonya Kebaya. The finding of this research will be useful to strengthen the sense of identity among Malaysians specifically the Malay and Baba Nyonya community. It is anticipated that the results of this research can become a source of reference in preserving and documenting Baju Kebaya as a national attire or costume, as part of the country’s cultural heritage and transmit the knowledge of intangible cultural heritage academically.